Molecular markers associated to downy mildew [Peronosclerospora philippinensis (W. Weston) C.G Shaw] resistance in Sugarcane (Saccharum officinarum L.) hybrids (CP 57-604 X PHIL 84-77) (The Philippine Journal of Crop Science, 2013)
Downy mildew is one of the major diseases of sugarcane that reduces cane yield. The disease is caused by Peronosclerospora philippinensis (Weston) C.G. Shaw which is commonly found in the Philippines. This study was conducted to identify molecular (SSR) markers that are linked with downy mildew resistance in a selected population of sugarcane. Hybridization between CP 57-604, a susceptible but high yielding variety and PHIL 84-77 a resistant and moderately high yielding variety was done. The field experiment was conducted mainly to screen the parents and the 100 progenies for the reaction to downy mildew, and to measure other important morphological characters of sugarcane. The experiment was laid out in a simple lattice design with two replications. The disease responses of the parents, as well as its progenies, were scored based on the rating scale given by International Society of Sugarcane Technologist (ISSCT). Considerable degree of resistance were found in progenies 1,2,4,10,11,13,16,30,35,36,40,44,49,51,65,66,67,68,70,71,79,81,83. And 95, whereas progenies 53 and 78 were found susceptible. The entries identified as resistant had the highest correlation coefficient of 0.86 between disease severity and disease response at week 5 and 6. The disease reactions of the population were used in marker analysis using 5 SSR sugarcane markers that were previously identified to be associated to downy mildew resistance. Phenotype data and SSR banding profiles of the population were subjected to UPGMA using Nei (1978) unbiased genetic identity to determined the clustering of the disease resistant and susceptible traits. PHIL 84-77 and the resistant progenies were clustered in group 1, while CP 57-604 and the susceptible progenies were clustered at group 2. Of the 5 markers for sugarcane and 48 rice microsatellites evaluated, 4 markers for sugarcane and 2 rice microsatellites were polymorphic across the screened genotype. Sugarcane marker mSSCIR12 generated 5 alleles and found to be highly informative with PIC value of 0.82. Since mSSCIR12 can generate polymorphic bands, this marker can be utilized in mapping sugarcane genotypes for downy mildew resistance. It is also possible to map sugarcane genotypes and germplasm for other traits of interest. Haplotype analysis of 100 progenies of sugarcane developed from the cross between CP 57-604 and PHIL 84-77 was conducted. Genotypes 35 and 51 were found to be resistant to downy mildew based on phenotypic evaluation and haplotype analysis.